Значение длины очереди автомобилей перед светофорным объектом и современные подходы к ее оценке - Sergey Vladimirovich Vitolin (Вестник СибАДИ, 2017)
This research offered the method of the increasing of general signalized intersections capacity by the installing of the short turning lanes on traffic light objects in Russian cities. Here showed an example of bottleneck effect at the signalized intersection as a result of wrongly matching for the short turning lanes. Also represented the importance of the vehicle queue length assessment in front of traffic light objects. Moreover some modern approaches to a queue length assessment are considered.